Dynamic Link Between Stock Market Size and Stock Market Investment Returns In Nigeria - Babarinde, Gbenga Festus (Accounting Department,, 2022)
Purpose—This study examines the dynamic link between stock market size and investment returns in Nigeria. Design/Methodology: Based on an ex post facto research design, the Autoregressive Distributed Lag (ARDL) technique was applied to the annual time series data obtained from the Central Bank of Nigeria’s statistical bulletin for the period 1985 to 2019. Findings– Findings indicate a negative, weak, and significant correlation and a long-run relationship between stock market size and stock market returns in Nigeria. Furthermore, this study confirmed that in the long run, the stock market size negatively and significantly affects stock market returns in Nigeria. However, in the short run, the effect of stock market size on returns is positive and statistically significant. Practical Implications–It is imperative that the government vigorously pursue capital market policies directed at expanding the market size in close partnership with the organized private sector. In contrast, the long-run negative effect of stock market size on stock market investors should be mitigated by improving the financial market environment in the areas of law and policy framework, professionalism and ethical operations, infrastructural improvements, etc. Original Value—This study posits that there is a significant negative long-run relationship between size and investment returns in the Nigerian Stock Exchange, and this relationship has long-term policy implications for the economy. Keywords– All-share index, Autoregressive Distributed Lag, Investments, Market capitalization, Stock market size, Stock returns. Paper Type—Research paper